Fabrication of high energy density supercapacitor device based on hollow iridium oxide nanofibers by single nozzle electrospinning - Beknalkar, S. A.; Teli, A. M.; Harale, N. S.; Patil, D. S.; Pawar, S. A.; Shin, J. C.; Patil, P. S. (Applied Surface Science, 2021)
Herein, we have synthesized iridium oxide (IrO2) nanofibers using electrospinning technique and optimization of annealing temperature is undertaken in order to obtain high quality IrO2 nanofibers. The annealing temperature is varied as 200, 300, 400 and 500 degrees C. The synthesized material has hollow nanofibrous morphology with average diameter similar to 45 nm. The formed nanofibers are amorphous in nature. The X-ray Photoelectron Spectroscopy (XPS) result revealed that synthesized iridium is in +4 oxidation state. The electrochemical performance of IrO2 electrodes showed 2 V potential window in three electrode system using 1 M Sodium sulphate (Na2SO4) aqueous electrolyte. The maximum specific capacitance is obtained for sample annealed at 400 degrees C (705F/g at 1 mA/cm(2)) which is due to the well-developed morphology with complete removal of polymer content. Moreover, a novel solid state symmetric IrO2/IrO2 supercapacitor with a high operating voltage of 2 V is built. The symmetric supercapacitor exhibits an energy density of 59 Wh/kg at a power density of 714 W/kg and an excellent cycling stability. These results demonstrate the potentialities of using IrO2 for symmetric supercapacitor for building high energy and power density devices.
Keywords: Aqueous electrolyte; Hollow iridium oxide nanofibers; Symmetric supercapacitor